KOMUNIKASI TERAPEUTIK ISLAMI DALAM PELAYANAN KESEHATAN PASIEN DI RUMAH SAKIT AL HUDA GENTENG - Nur Hafifah (Indonesian Journal of Islamic Communication, 2019)
This study aims to know the forms of therapeutic communication conducted by doctors and paramedics in Patient Health Services, especially toward patients in one of the Islamic hospitals in Banyuwangi, namely Al Huda GentengBanyuwangi. This study also signifies the application of communication therapeutic performed by doctors and paramedics on patients in order to provide the best health services and find an overview of the patient's response to the application of therapeutic communication applied with the principles of Islamic Communication. The theoretical framework used in this study is the Interpersonal Communication Theory proposed by Joseph A. Devito, Therapeutic Communication Theory initiated by Hildegard Peplau, and also the Theory and principles of Islamic Communication based on the Al Qur'an. This study uses a qualitative descriptive approach. The technique of data collection is observation, in-depth interviews, literature studies, and documentation. The Informants in this study were doctors and paramedics as communicators in the process of therapeutic communication and patients as communicants or recipients of therapeutic communication services. The data is processed using the Miles and Huberman models, namely through three steps, the first is data reduction, the second step is presenting the data, and the last stage is the conclusion. The results of the research revealed that forms of therapeutic communication carried out by doctors and paramedics/ nurses towards patients in the orientation phase, working phase and phase of termination were through interpersonal communication with the delivery of messages through forms of verbal communication, written communication, and nonverbal communication. The form of verbal communication is implemented through clear and concise dimensions, vocabulary, pauses and speaking opportunities, the meaning of denotative and connotative appropriate time, and also relevance humor. The form of written communication is carried out through letters, memos, prescription drugs with attention to clarity and accuracy of messages, and forms of nonverbal communication carried out through self-appearance, tone of voice, facial expressions, and touch. All forms and dimensions of interpersonal communication have not been applied and provided by doctors and paramedics/nurses, as well as the principles of Islamic communication which have not implemented optimally. It also does not become a guideline in providing health services to patients in Islamic hospitals in GentengBanyuwangi yet. Keywords: Islamic Therapeutic Communication, Principles of Islamic Communication, Patient Health Services.